THE EFFECTIVENESS OF USING RANDALL’S ESL CYBER LISTENING LAB IN TEACHING LISTENING COMPREHENSION - Dwi Wahyuningsih; Delsa Miranti; Eri Rahmawati (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2018)
The objective of this research is to find out whether Randalls‟ ESL Cyber Listening Lab as a teaching media for listening is effective for students‟ listening comprehension at the eleventh grade of SMA PRISMA Kota Serang. The researcher used quantitative research by using true experimental design. The population of this research is all students at eleventh grade of SMA PRISMA Kota Serang. The sample were divided into 2 classes, they were XI IPS 1 as the experimental class and XI IPS 2 as a control class. Each group consists of 20 students. Then, the result showed the significance degree of 5%. The result was t_count > t_table (82.05 > 2.02), it means that the null hypothesis (H_o) is accepted. This indicates that Randalls‟ ESL Cyber Listening Lab is effective to be used as a media for students‟ listening comprehension at the eleventh grade of SMA PRISMA Kota Serang.